STUDI EVALUASI TAMAN KOTA SEBAGAI TAMAN TERAPEUTIK STUDI KASUS: TAMAN CILAKI ATAS, KOTA BANDUNG - Azi MA Hidayah; Qodarian Pramukanto (http://arl.faperta.ipb.ac.id/, 2011)
Urban park have some functions. There are ecology, aesthetics, and social functions. Many parks in Indonesia still have not been utilized as a health environment function. Therefore, it is important to identify potency of potential an existing condition of urban park as a therapeutic park. The objective of study is to evaluate the potency of Cilaki Urban Park, Bandung City, West Java as therapeutic park. The study was started with inventoryand analysis of biophysics, site quality, spatial, site element, user and their activities. Key Performance Index (KPI) method was used to evaluate an existing condition of the park based on modified therapeutic design criteria proposed by some Landscape Architects. Questionnaire was used to confirmsome respondent’s expectations about urban and therapeutic function, and then, the direct observation data used as a verification user’s activities. The result showed that the KPI’s value was 0.61 (scale 0-1), so this urban park has some potentials as a therapeutic urban park. The last result of this study is recommendations based on evaluation among KPI’s value, user’s confirm and surveyor’s verification.